Phraseological units and communicative competence: set phrases - Quintanilla Anglas, Rómulo F. (2011)
One of the resources speakers of Spanish and other languages usually employ in the communication process, especially in the oral aspect, is that of phraseologicaJ units (PU). Among these units, some like metaphors, idioms or paremias (sayings, proverbs, idioms, quotations, maxims, adages, aphorisms, slogans) are frequently used in situations of real or natural (colloquial) conversation, no matter what the topic of communication is. These units studied by lexicography occur, practically, in all natural languages, as shown by our bibliographic research, as well as by our collection of synchronic oral data. The Spanish language used in Peru also presents these units, which have fixed, complex structures, and some, such as idioms, topic of the present article, have a lexical value, and, as such, perform syntactic functions in their relationship with other simple linguistic units.